Exploring the determinants of destination satisfaction: a multidimensional approach - Ubais Parayil Iqbal; V. K. Hamza; Lenin Kumar Nooney; Shajeer Sainudeen (Future Business Journal, 2023)
Abstract Tourism, as one of the major contributors to the world GDP, offers a wide range of economic and non-economic benefits to global society. The exchange of culture and values through travel and tourism improves harmony among people, which is essential for global peace. Consequently, governments have started giving policy significance to the tourism sector and making budget allocations for its promotion in their respective countries. This increased attention on tourism promotion through policy initiatives has fostered research attempts on various aspects of tourism, making it relevant and contemporary. However, few research attempts have been made to study the precursors of destination satisfaction. Therefore, the present study aims to fill this gap by studying the determinants of destination satisfaction through a multidimensional approach. The current study aimed to examine the dimensions of destination satisfaction and its role in deciding the destination loyalty. The study reveals interesting findings that helps the administrative apparatus in the tourism industry to come up with tailor-made policies to sustain and further enhance economic growth. The study findings reveal that factors such as satisfaction with destination characteristics, destination environment, and price significantly influence destination satisfaction among tourists visiting the Maldives. These findings underscore the importance of price as a determining factor in tourists' decision to visit the Maldives, suggesting the promotion of guesthouse tourism to provide a range of price options to attract a diverse tourist base. Additionally, the study emphasizes the necessity to enhance the quality of destination characteristics and prioritize environmental conservation efforts to ensure a positive tourist experience. The results highlight the important dimensions that determine the destination satisfaction of tourists visiting Maldives.